Recreating Burmese cinema through travelling and tracing via deconstruction - Ma Ei Thandar Soe (2013)
The word "cinema" comes from the Greek word "kinema" which means "motion". The word "theory" too, comes from a Greek word "theoria" which means to "see the sights or to see something for yourself"(Walter 18). In this essay, we will look at the mobility of Burmese cinema. To do so, we must first "theorise" Burmese cinema, look at how this cinema has captured the Burmese social, political, economical, artistic and cinematic movements and then expand out to see if this house of "motion" picture has been able to progress elsewhere outside of Burma. In principle, finding out if Burmese cinema has actually travelled.